Estudo do impacto da consideração de custos de emissão de CO2 nas decisões de planejamento e roteamento de veículos de uma fábrica de móveis - Moraes, Felipe Goulart (Universidade Federal de São Carlos, 2023)
At the same time that the competitive scenario is seen in organizations, which seek to maximize profits and consumer satisfaction, there are also global concerns about increasing productivity and its impact on the environment, such as the emission of greenhouse gases, mainly CO2. To assist in decision-making and achieve reduction of economic and environmental costs, linear modeling and optimization techniques can be adopted and implemented. Through these techniques this dissertation aims to study the problem of integrated production planning and vehicle routing considering the impacts of reducing carbon emissions in furniture industries. The consideration of carbon emissions is linked to vehicle fuel emissions and applying this view brings a more realistic scenario as it considers the load transported in vehicles and speeds. Through experiments will be analyzed the gains from considering the unloading of vehicles, the speed selection that the vehicle adopts and how much the inclusion of carbon costs can affect the trade off between production and routing. An additional model was also developed that considers a heterogeneous fleet in relation to CO2 potential emission
Study of the impact of considering CO2 emission costs on vehicle planning and routing decisions in a furniture factory
Keywords: Pollution Production Routing Problem; Otimização Linear Inteira Mista; Indústria de Móveis; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL